Depicting the Tumor Associated Macrophege phenotype employing 3D Breast Cancer Cell Models - Lopes, Nuno Filipe Lavos (2018)
The tumor microenvironment (TME) plays an important role in tumor progression and therapy resistance. Within the TME, tumor associated macrophages (TAM) can represent up to 50% of all components, being usually associated with the most aggressive breast cancer (BC) subtypes, such as Her2 overexpressing (HER2+) and triple negative. Several reports suggest that TAM contribute to the establishment of an immunosuppressive microenvironment, which enhances tumor immune evasion and progression . In this thesis, the ultimate aim was to contribute to characterize the TAM phenotypes associated with different BC subtypes. To attain that, a cell-based BC model was implemented, based on co-cultures of BC cell lines (BT474 and HCC1954, representing the Luminal B and HER2+ subtypes, respectively) and human blood derived monocytes. Cancer cell spheroids and monocytes were co-encapsulated in alginate and cultured in stirred-tank vessels for 7 days. After this time, monocytes differentiated into macrophages, as shown by the detection of CD206 and CD163. Moreover, high detection of CD206, CD163 and low detection of CD80 suggested differentiation into M2-related phenotypes. Further, when comparing the impact of the BC cell lines on monocyte differentiation, the M2-related markers detection was higher in macrophages cultured with HCC1954, suggesting that this cell line may induce more mature M2-like populations. These differences were corroborated by distinct cytokine secretion profiles in both co-cultures: while for HCC1954, IL-4, IL-13, VEGF and CCL2 were increased, for BT474 there was higher secretion of IL-10, CCL24 and TGF- β. Finally, fibroblasts were introduced into culture, to represent the tumor stroma. In their presence, macrophages showed higher expression of M2-like markers, compared with double co-cultures. In conclusion, in this thesis a 3D cell-based model to depict BC-macrophage crosstalk was established. Moreover, the microenvironment established in the model promoted naïve monocytes differentiation into M2-like phenotypes, suggesting that this may be a useful tool to understand the induction of different TAM phenotypes in distinct BC subtypes